Capacity Building Camat Dalam Melakukan Pembinaan Kepala Desa Di Kecamatan Kerinci Kanan Kabupaten Siak - zainal zainal (Departemen Ilmu Pemerintahan Fisip Unhas, 2022)
The problem with this research is the lack of capacity building for the sub-district head in coaching village heads so that there are still some village heads who do not understand how to carry out their duties. The purpose of this study was to find out how the quality of the Camat's Capacity Building in Conducting Village Head Coaching in Kerinci Kanan District, Siak Regency. This study used qualitative research methods. The indicators in this study are human resources, organization and institutional reform. The use of this qualitative method aims to support the level of results so that they can be accounted for and easy to understand. This research data collection instrument prioritizes interviews as a means of obtaining the main raw materials to obtain appropriate results. The key informants of this research were the Kerinci Kanan Sub-district Head, Kerinci Kanan Village Head, Kerinci Kiri Village Head, Bukit Agung Village Head, and one of the people from each village. Based on the results of the discussion, it can be concluded that capacity building is not a process that starts from scratch but starts from building existing potential and then processed to further improve the quality of self, groups, organizations, and systems in order to survive in an environment that undergoes continuous change by utilizing cooperation between sub-district apparatus with village apparatus.